2019
DOI: 10.51386/25815946/ijsms-v2i5p104
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Employee Engagement and Individual Well-Being on Organisational Performance in Nigeria

Abstract: This study measures the significance of employee engagement and individual well-being on organisational performance. The collected data was done through the administration of semi-structured questionnaires and interview. The researchers gathered data from one of Nigeria’s top manufacturer of plastics. A total number of 48 questionnaires were administered to the staff of the selected organisation. Correlation analysis was used to test the hypotheses to measure the specified variables. The result shows that empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Employees with ten or more years of experience, on the other hand, have developed routines and may not prioritize continuous learning, which resulted in lower scores in perceptions of learning and knowledge, organizational culture, leadership, situation awareness, and risk management. This is in line with the assertion of Adekoya et al (2019) that employee satisfaction and wellbeing have a major impact on productivity and effectiveness, both of which have the power to improve business performance. In order to ensure efficiency and improved performance in their organization, it was advised that top management of organizations should consider a variety of drivers of employee engagement, including empowering the employees, providing full information, top management support, and aligning efforts with strategy.…”
Section: Organizational Resilience and Hrmp Of Accommodation Establis...supporting
confidence: 89%
See 1 more Smart Citation
“…Employees with ten or more years of experience, on the other hand, have developed routines and may not prioritize continuous learning, which resulted in lower scores in perceptions of learning and knowledge, organizational culture, leadership, situation awareness, and risk management. This is in line with the assertion of Adekoya et al (2019) that employee satisfaction and wellbeing have a major impact on productivity and effectiveness, both of which have the power to improve business performance. In order to ensure efficiency and improved performance in their organization, it was advised that top management of organizations should consider a variety of drivers of employee engagement, including empowering the employees, providing full information, top management support, and aligning efforts with strategy.…”
Section: Organizational Resilience and Hrmp Of Accommodation Establis...supporting
confidence: 89%
“…The respondents also had a favorable opinion of the management. Adekoya et al (2019) noted that employee satisfaction and wellbeing have a major impact on productivity and effectiveness, both of which have the power to improve business performance. Moreover, as discussed by Fu et al (2023) found that companies with happier employees have lower equity costs.…”
Section: Organizational Resilience and Hrmp Of Accommodation Establis...mentioning
confidence: 99%
“…It is significant that the study by Bailey et al (2015) was metanalytic in nature and was based on 214 empirical studies. Considering that WE can enhance efficiency and effectiveness and resultant performance (Adekoya et al, 2019;Armstrong et al, 2016), the findings of this study are significant.…”
Section: Discussionmentioning
confidence: 83%
“…Bailey et al (2015), based on 214 studies, identified a robust relationship between WE and task performance. Adekoya et al (2019) found WE and WWB to enhance efficiency, effectiveness, and resultant performance significantly. A few other researchers also found a significant association between WE and performance (Armstrong et al, 2016; Ellis & Sorensen, 2007).…”
Section: Review Of Literaturementioning
confidence: 96%
“…Diminished levels of employee well-being are linked to reduced productivity, increased rates of absenteeism, and elevated turnover. Recognizing the profound impact of employee engagement, organizations actively seek to cultivate high engagement levels, foreseeing positive ramifications for productivity, innovation, profitability, and employee commitment (Adekoya, Jimoh, Okorie, & Olajide, 2019). A recent investigation by Bryson, Forth, and Stokes (2017) further underscores the interconnection between job satisfaction and job performance, highlighting that heightened job satisfaction positively contributes to increased job performance, thereby enhancing overall organizational productivity.…”
Section: Economic Impactmentioning
confidence: 99%